2018
DOI: 10.1016/j.ijrobp.2018.06.177
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Case-Control Analysis of Clinical Outcomes for Inflammatory Bowel Disease Patients with Rectal Cancer Treated with Pelvic Radiation Therapy

Abstract: patients had tumoral PD-L1 expression !5%. Patients with tumoral PD-L1 !5% had better OS vs those with lower expression, HRZ0.29 (CI 0.10-0.78), pZ0.009; 10 years OS: 84% for PD-L1 !5% vs. 46% for PD-L1 <5%. On univariate analysis, OS was associated with PD-L1 status, as well as T stage, N stage, ECOG status and gender. On multivariate analysis, PD-L1 !5% remained statistically significant for better OS, HRZ0.35 (CI 0.12-0.99), pZ0.047. 33 of 65 (51%) of tumors had high CD8 levels (3 or 4). There was no associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…11 There was a SS higher rate of SBO (OR 15, 95% CI 1•9-115, p = 0•009) and higher rates of abdominopelvic adhesions that approached statistical significance (OR 3•6, 95% CI 0•98-13, p = 0•05) in the IBD þ RT cohort. 11 When compared to the nonmatched cohort with IBD treated without RT, there was no difference in long-term complications, suggesting that these adhesions or obstructions may be unrelated to RT. 11 Chang et al reported on 15 anal/rectal cancer patients with IBD treated with EBRT.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…11 There was a SS higher rate of SBO (OR 15, 95% CI 1•9-115, p = 0•009) and higher rates of abdominopelvic adhesions that approached statistical significance (OR 3•6, 95% CI 0•98-13, p = 0•05) in the IBD þ RT cohort. 11 When compared to the nonmatched cohort with IBD treated without RT, there was no difference in long-term complications, suggesting that these adhesions or obstructions may be unrelated to RT. 11 Chang et al reported on 15 anal/rectal cancer patients with IBD treated with EBRT.…”
Section: Resultsmentioning
confidence: 89%
“…Reported late toxicities in prostate cancer studies are also reported in Table 3B, with a range for late toxicity ≥ grade 2 of 6•3-17% for EBRT (2 studies reporting) and 0-38% for brachytherapy (4 studies reporting), and late toxicity ≥ grade 3 of 0% (1 study reporting) for EBRT and 0-15% for brachytherapy (3 studies reporting). When looking at those studies that only included gastrointestinal (GI) primary malignancies [9][10][11][12] , namely rectal and anal cancers, the reported range for acute toxicity ≥ grade 3 was 0-28% and the late toxicity ≥ grade 3 was 13% (Table 3B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations